Preferences of Integrated Care and the Influencing Factors Among Chinese Community-Dwelling Older Adults - Liu S; Zhao J; Liu N; Qin T; Wang F (Patient Preference and Adherence)
Siqi Liu,1,* Jun Zhao,1,* Nan Liu,1 Tingting Qin,2 Fang Wang3 1Center of Health System and Policy, Institute of Medical Information & Library, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Science and Technology, Beijing Shijitan Hospital, Capital Medical University, Beijing, People’s Republic of China; 3School of Health Policy and Management, Peking Union Medical College, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Wang, School of Health Policy and Management, Peking Union Medical College, No. 9 Dongdan 3rd Alley, Dongcheng District, Beijing, 100730, People’s Republic of China, Email wang.fang@imicams.ac.cnObjective: Population aging and epidemiological transition have prompted requests for integrating health and social care. The goal of meeting complex care needs necessitates the understanding of preferred patterns among older adults. The study aimed to elicit the preferred care patterns and the influencing factors of integrated health and social care among community-dwelling older adults in multiple regions of China.Methods: From a national survey, 1184 community-dwelling older adults in three cities across China were included in the study. Individual characteristics and preferred care patterns were measured. Five preferred care patterns were classified, including Home-based health and social care, Community-based health and social care, Home-based health care but community-based social care, Community-based health care but home-based social care, and Institution-based health and social care. Multivariate logistic regression and random forest model were applied to obtain reliable results.Results: Overall, approximately half of the participants (47.7%) in the survey preferred Home-based health and social care and more than a quarter of participants (25.6%) preferred Community-based health and social care, followed by Institution-based health and social care (14.4%). A relatively small fraction of participants reported preferences for Home-based health care but community-based social care (8.0%) and Community-based health care but home-based social care (4.2%). Gender, age, education, living arrangement, resident city, income per month, access to medication, and self-care capability were significantly associated with older adults’ preferences (p< 0.05 each). Education, living arrangement, age, resident city, and income per month were the most relevant predictors, followed by gender, number of chronic diseases, self-care capability, and access to medication.Conclusion: To effectively meet care needs, efforts should focus on home- and community-based care. Since the preferred care patterns were characterized by obvious variability, policymakers and service providers should carefully consider the differences in making tailored strategies.Keywords: health care, social care, home- and community-based settings, preferred care patterns